Assessment of structural shifts in youth employment in Kazakhstan - Gazizova, M.R.; Khusainova, Zh.S.; Vechkinzova, Y.A.; Sarzhanov, D.K. (KU Publ., 2021)
Object: Based on the assessment of structural changes in youth employment in Kazakhstan to identify favorable industries for the development of the labor activity of young workers. Methods: Methods of system, dynamic and structural analysis, estimates of the mass of structural shifts have been used. Results: The results of the analysis of changes in structural shifts in youth employment facilitated to identify the most favorable industries in the labor activity of this age group: agriculture, forestry and fisheries, professional, scientific and technical activities, public administration and defense, compulsory social security, education, human health and social work activities, other service activities. Conclusions: Based on statistical data on the employment of the population aged 15–28 years in Kazakhstan, favorable industries for the continuation of youth work have been identified. Measures of state support for youth employment can be aimed at the identified industries as favorable for youth work in the future, thereby reducing youth unemployment and NEET-youth indicators.
Assessment of structural shifts in youth employment in Kazakhstan
Оценка структурных сдвигов в сфере занятости молодежи в Казахстане
Keywords: labor market; youth; youth employment; structural changes; economic activity; youth unemployment